2017
DOI: 10.1111/irv.12498
|View full text |Cite
|
Sign up to set email alerts
|

Influenza‐associated mortality in South Africa, 2009‐2013: The importance of choices related to influenza infection proxies

Abstract: BackgroundRegression modeling methods are commonly used to estimate influenza‐associated mortality using covariates such as laboratory‐confirmed influenza activity in the population as a proxy of influenza incidence.ObjectiveWe examined the choices of influenza proxies that can be used from influenza laboratory surveillance data and their impact on influenza‐associated mortality estimates.MethodSemiparametric generalized additive models with a smoothing spline were applied on national mortality data from South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Generalised additive models (GAMs) have been used in multiple studies for estimating influenza burden. 4,8,16,17 An advantage of the GAM is that it allows the data to suggest an appropriate functional form for the relationship between an explanatory variable and the response using a penalised likelihood function. 26 We also included a spline function to account for the non-linear long-term time trend.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Generalised additive models (GAMs) have been used in multiple studies for estimating influenza burden. 4,8,16,17 An advantage of the GAM is that it allows the data to suggest an appropriate functional form for the relationship between an explanatory variable and the response using a penalised likelihood function. 26 We also included a spline function to account for the non-linear long-term time trend.…”
Section: Discussionmentioning
confidence: 99%
“…We used a generalised additive negative binomial model to estimate the weekly number of P&I hospitalisations associated with influenza during the 8‐year study period. Generalised additive models (GAMs) have been used in multiple studies for estimating influenza burden . An advantage of the GAM is that it allows the data to suggest an appropriate functional form for the relationship between an explanatory variable and the response using a penalised likelihood function .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen population‐specific articles have been included in this Special Edition—including five from Asia, four from Africa, four from Europe, three from North America, and one each from South America and the Middle East . (Figure and Table ) This reflects a broad geographical breadth of new research, and these data will add to our understanding of the burden of disease worldwide, especially in LMICs.…”
Section: New Series Of Burden Studiesmentioning
confidence: 99%
“…The study from India found that while the Sample Registration System provided the most appropriate national mortality data set, other mortality data sources could be used for subregional estimates . The South African study showed that weekly proportion and influenza subtype‐specific proxies provided the best model fit with non‐significant differences in the estimates …”
Section: New Series Of Burden Studiesmentioning
confidence: 99%